#TITLE_ALTERNATIVE# - (NIM : 12208067), FAHRUDIN
Drilled cuttings, which is defined as generated micro-scale formation rock during drilling process, should be circulated to surface continuously, this process also called hole cleaning. Poor hole cleaning performance lead many disadvantages, i.e. cutting precipitation in the wellbore could reduce rate of penetration. Drilling fluid plays an important role in circulating system, and the major aspect affecting hole cleaning performance, since cutting circulated to surface through it. Physical properties and volumetric rate of drilling fluid helps to be able to hold and circulate cutting along with flow to surface. The main idea of aerated mud is to reduce annular circulating pressure by adding lighter phase (gas) into conventional (liquid) mud system. This addition affects physical properties of mixture in the mud system. Reduction of circulating pressure considered when drilling operation deal with depleted formation bottom hole pressure and or loss circulation zones. Determination of mixture physical properties in the mud system, then become more complex caused by compressible behavior of gas phase, which is depend on pressure and temperature. Gas expansion lead the tendency of gas phase to flow faster than liquid phase. Thus, as a result of slip-flow phenomena in the mixture, also affect the flow pattern that possibly occurs in the wellbore. Different flow pattern gives different pressure losses prediction through the annulus. In this study, multiphase flow pattern modeling is performed first for later use to analyze cutting transport parameters in aerated mud circulating system. Then, by considering bottom hole pressure target and hole cleaning criteria, operating design is determined. Another objective of this study is, sensitivity analysis of parameters affecting hole cleaning performance.